2020
DOI: 10.1080/22423982.2020.1832390
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary clinical algorithm to optimise remote delivery of paediatric concussion care in Canada’s North

Abstract: Concussion is a form of traumatic brain injury that affects thousands of children and adolescents across Canada annually. With timely access to comprehensive medical care, the majority of patients with acute concussion will recover within 1-4 weeks. Those who develop persistent postconcussion symptoms often benefit from early recognition and referral to multidisciplinary concussion clinics that have the personnel and resources to meet their complex needs. Youth who live in remote and isolated communities withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…The differences in the urgency assessment were also related to respiratory rate, heart rate or pain, oxygen saturation, the Glasgow coma scale and trauma injuries. This study confirms that trauma cases should be assessed very carefully when employing telemedicine [ 15 , 16 , 30 ]. Undertriage is a serious problem that requires specific attention in a follow-up study.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The differences in the urgency assessment were also related to respiratory rate, heart rate or pain, oxygen saturation, the Glasgow coma scale and trauma injuries. This study confirms that trauma cases should be assessed very carefully when employing telemedicine [ 15 , 16 , 30 ]. Undertriage is a serious problem that requires specific attention in a follow-up study.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, in a real healthcare setting, overtriage could lead to unnecessary transfers to another hospital or unnecessary examinations. However, other studies have shown that telemedicine reduced the number of transfers and costs while still ensuring patients’ safety [ 10 12 , 14 , 15 , 18 ]. Cases in which the telemedicine doctor assigned a lower level of urgency than the on-site doctor (undertriage) should be evaluated more critically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20][21][22][23] More recently, a growing body of research has begun to demonstrate that telemedicine is a safe and cost-effective approach to delivering remote care to patients with concussion. [24][25][26][27] Similar to systems of care developed for acute stroke, 28,29 telemedicine-based networks centered around regional or provincial multi-disciplinary concussion clinics may be a novel approach to expand access to specialized care for patients living in remote, isolated, and medically underserviced communities throughout Canada. 30 Despite this innovative work, little is known about the use of telemedicine among Canadian concussion care providers and clinics, how use of this technology has changed during the COVID-19 pandemic, and what barriers must be overcome to promote greater adoption and sustainability of telemedicine to manage concussion.…”
mentioning
confidence: 99%